Monte Carlo simulation of Nd:YAG laser fluence distribution in human tissue - Gulsoy, M.; Kurt, A.; Cilesiz, I. (IEEE, 2002)
In this study, photon propagation is simulated by Monte Carlo algorithm, using absorption and scattering coefficients of histologically different human tissues (bone, brain white matter, liver, prostate, myocardium); fluence distribution is calculated by the convolved data, and comparisons are reported.